Scarcely an Immaculate Conception: New Professionalism Encounters Old Politics in the Formation of the Australian National History Curriculum. (1st May 2013) - Taylor, Tony
This paper deals with the political and educational background to the formation of the Australian national history curriculum first under the auspices of a newly-formed National Curriculum Board (2008-2009) and then under the auspices of the Australian Curriculum and Assessment Authority (2008-date) during the period 2008-2010. The author describes and analyses the political and educational circumstances that have led to interventions in the curriculum design process that may well vitiate the original intentions of the curriculum designers. The process of curriculum design began in 2008 with the formation of a professionally-based History Advisory Group of which the author was a member (2008-2012). The author outlines the activities and contribution of the History Advisory Group and its sometimes fraught relations with the Australian Curriculum and Assessment Authority. The author argues that these interventions which have been both political and educational, together with the well-intentioned process of consultation has led to unfortunate design changes and to politically-motivated delays in curriculum implementation which could lead to its being overturned by a successor conservative coalition government.